Price Sensitivity Analysis of Medium Quality Rice: Insights from Low to Middle Income Households in Gresik Regency, Indonesia - Firmansyah, Akbar Maulana; Humaidi, Taufiq Rahman; Nugrahaini, Amelia Dwi; Syahnaz, Cindiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study explores the price sensitivity of medium-quality rice among low- to middle-income households in Kota Baru Driyorejo, Gresik Regency, Indonesia, using the Van Westendorp Price Sensitivity Meter (PSM). Rice is the staple food for most Indonesians, particularly for low-income households where it fulfills essential caloric needs. This research identifies the acceptable price range for medium-quality rice, revealing critical thresholds: the Point of Marginal Cheapness (PMC) at Rp 10,000, the Point of Marginal Expensiveness (PME) at Rp 12,500, the Optimal Price Point (OPP) at Rp 11,000, and the Indifference Price Point (IPP) at Rp 11,500. These insights highlight the delicate balance between affordability and perceived quality, underscoring the need for strategic pricing to mitigate financial strain on vulnerable populations. A purposive sampling method targeted 335 respondents from households with monthly incomes of IDR 2,000,000 to IDR 3,500,000, ensuring the focus on those most affected by price fluctuations. The findings provide actionable guidance for policymakers and market stakeholders to develop equitable pricing strategies, stabilizing rice consumption and promoting food security. Future research should address production efficiency and expand the scope to other regions and demographics to refine pricing policies and their socioeconomic impact.